KANDUNGAN C-ORGANIK TANAH DAN TOTAL NITROGEN PADA TANAH VERTISOL YANG TELAH DIBAKAR DAN TIDAK DIBAKAR - Ana Juliana Ome; W.I.I Mella; Manuel Pian (AGRICA, 2012)
The use of fire in agriculture land preparation may result in the change of various soil properties. Therefore, a study was conducted in the village of Oeteta, Kupang to determine soil total organic-C and total nitrogen of burned and unburned Vertisols. Randomized complete block design with two factors was applied. The first factor was burning treatment with two levels: burned and unburned. The second factor was soil depth with three levels: 0-10cm, 11-20cm and 21-30cm; all together made up 54 experimental units. Results showed that in all depths there was no significant difference in total soil organic-C between burned and unburned soils. However total soil organic-C contents in both burning treatments were considered high. Similarly, the was also no significant difference in total soil nitrogen between burned and unburned plots. Total soil N was considered in high and medium levels for burned and unburned soil respectively. In summary, burning does not affect soil total organic-C contents but reduces soil total N contents.